1990
DOI: 10.1093/ajcn/51.2.241
|View full text |Cite
|
Sign up to set email alerts
|

A new predictive equation for resting energy expenditure in healthy individuals

Abstract: A predictive equation for resting energy expenditure (REE) was derived from data from 498 healthy subjects, including females (n = 247) and males (n = 251), aged 19-78 y (45 +/- 14 y, mean +/- SD). Normal-weight (n = 264) and obese (n = 234) individuals were studied and REE was measured by indirect calorimetry. Multiple-regression analyses were employed to drive relationships between REE and weight, height, and age for both men and women (R2 = 0.71): REE = 9.99 x weight + 6.25 x height - 4.92 x age + 166 x sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
1,553
13
42

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,069 publications
(1,647 citation statements)
references
References 15 publications
39
1,553
13
42
Order By: Relevance
“…This result is similar to other studies, which have compared this prediction method with measured BMR, showing that predictions underestimated true requirements (Hunter et al, 1988;Ahmad et al, 1999). Studies comparing measured BMR to BMR predicted by the Harris-Benedict equations in healthy adults have indicated that the equations consistently overestimate requirements, ranging from 104.8 to 113.5% (Daly et al, 1985;Owen et al, 1986Owen et al, , 1987Foster et al, 1988;Mifflin et al, 1990;Case et al, 1997). Few studies have compared the use of the Schofield equations in healthy adults.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This result is similar to other studies, which have compared this prediction method with measured BMR, showing that predictions underestimated true requirements (Hunter et al, 1988;Ahmad et al, 1999). Studies comparing measured BMR to BMR predicted by the Harris-Benedict equations in healthy adults have indicated that the equations consistently overestimate requirements, ranging from 104.8 to 113.5% (Daly et al, 1985;Owen et al, 1986Owen et al, , 1987Foster et al, 1988;Mifflin et al, 1990;Case et al, 1997). Few studies have compared the use of the Schofield equations in healthy adults.…”
Section: Discussionsupporting
confidence: 86%
“…The importance of estimating energy requirements has been well documented and many researchers have attempted to develop prediction equations for use when direct measurement is not possible (Harris & Benedict, 1919;Schofield, 1985;Owen et al, 1986Owen et al, , 1987Mifflin et al, 1990;Vinken et al, 1999). This study aimed to determine current methods used by Australian dietitians for estimating energy requirements of patients and the variability of the outcomes of the calculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows the scatter diagrams redrawn from the publication A Biometric Study of Basal Metabolism in Man (1919). Despite the limited number of subjects older than 50 y, the simplicity of the Harris ± Benedict equation made it a popular equation widely used even today by many clinicians in North America (Daly et al, 1985;Roza & Shizgal, 1984;Mif¯in et al, 1990). Harris and Benedict (1919) …”
Section: Equations To Predict Bmr In the Elderlymentioning
confidence: 99%